Theoretical Analysis Model of the Adoption of Reactive and Proactive Eco-Innovation Strategies: the Influence of Contextual Factors Internal and External to Organizations - Marlete Beatriz Maçaneiro; Sieglinde Kindl da Cunha (BBR: Brazilian Business Review)
This article aims to provide research propositions of the relationship between internal and external contextual factors and strategies for reac tive and proactive eco-innovation, defining the theoretical analysis model from these propositi ons. Therefore, this study is characterized as a theoretical essay, adopting the methodological procedure of literature review, through an analysis of national and international articles on the subject of eco-innovation strategy. As a result, the external and internal factors that affe ct the adoption of eco-innovation strategies were defined and propositions were made for their r elationship. With this theoretical approach and the establishment of the factors, it was possib le to design the theoretical model to analyze the impact of contextual factors on the adoption of eco-innovation strategies.